Clinical utility of dental cone-beam computed tomography: current perspectives - Jaju PP; Jaju SP (Dove Medical Press, 2014)
Prashant P Jaju,1 Sushma P Jaju21Oral Medicine and Radiology, 2Conservative Dentistry and Endodontics, Rishiraj College of Dental Sciences and Research Center, Bhopal, IndiaAbstract: Panoramic radiography and computed tomography were the pillars of maxillofacial diagnosis. With the advent of cone-beam computed tomography, dental practice has seen a paradigm shift. This review article highlights the potential applications of cone-beam computed tomography in the fields of dental implantology and forensic dentistry, and its limitations in maxillofacial diagnosis.Keywords: dental implants, cone-beam computed tomography, panoramic radiography, computed tomography